Analisis Kepemimpinan Dan Budaya Organisasi Dalam Meningkatkan Kinerja Tim Dopamine Screen Printing - Cinta Taufatul Ummah; Ardista Dwi Elsania; Naflah Aurellia Nabilah Firzatullah; Insyirohul Qulub Al Afthoni; Muzizah Nur Fitri; Bagus Hari Prasetya; Duwi Purnasari (Shofanah Media Berkah, 2025)
This study aims to analyze how leadership and organizational culture contribute to improving team performance at Dopamine Screen Printing. The main issues identified in this context relate to the diversity of employee characteristics, challenges in managing differences in work behaviors, and operational pressures arising from the high volume of orders and varying customer characteristics. This study employed a descriptive qualitative approach through in-depth interviews with the owner and employees, direct observation of the work environment, and documentation review, which was then transcribed for analysis. The results indicate that a flexible leadership style combines gentleness and assertiveness, adapting to individual employee needs and providing clear direction for tasks and responsibilities. An organizational culture that emphasizes discipline, open communication, strong implementation of Standard Operating Procedures (SOPs), and mutual reminders successfully creates an adaptive and productive work environment. Furthermore, the team's ability to cope with deadline pressures, diverse customer characteristics, and negotiation needs demonstrates the importance of inter-divisional coordination and interpersonal intelligence. These findings confirm that integrating adaptive leadership and a supportive organizational culture is an effective solution for improving team performance in the printing services business.